Seasonal and Spatial Differences in Metal and Metalloid Concentrations in the Snow Cover of Hansbreen, Svalbard - Koziol, Krystyna; Uszczyk, Aleksander; Pawlak, Filip; Frankowski, Marcin; Polkowska, Żaneta (Frontiers in Earth Science, 2021)
Metals and metalloids in snow on glaciers, depending on the season of deposition, may come from various sources: local rock dust (erosion of the geological substratum), marine aerosol, local human activity (e.g., impurities in combusted fuel and waste incineration), and long-range atmospheric transport. Hansbreen, a glacier located close to the Polish Polar Station in southern Svalbard, is a perfect site to study metals and metalloids: it has a complex geological substratum, has a year-round presence of a small group of people, and is near the coast. We analyzed a snapshot of metal and metalloid concentrations in snow samples from shallow cores corresponding to autumn, winter, and spring deposition on Hansbreen. Eighteen cores of snow were collected across the glacier, revealing the influence of potential local sources of metals and metalloids. In these samples, we predominantly found Na, Mg, and K, followed by Zn, Ca, Al, and Fe. Heavy metals, such as Bi or Hg, were also detected. Cluster analysis of the determined elemental concentrations divided them into three distinct groups: Group 1: Ag, As, Bi, Cd, Hg, Mo, Sb, Se, and Zn—the most diverse cluster, representing mostly long-range transported volatile elements, with possible extra local geological sources; Group 2: Al, Fe, Cu, and Mn—elements with crustal sources; and Group 3: Na, Ca, Mg, K, and Sr—with the main source in sea spray aerosol. The latter interpretation was confirmed by the calculation of sea salt contribution based on the composition of mean seawater and the positive significant correlation between their concentrations and the electrical conductivity of snow samples. In the study site, snow was up to six times more efficient in bringing metal pollution into terrestrial environment, when compared to rain.